Methodology of organizing autonomy in professionaly-based dialogical speech learning for future spesialists in the service sphere (german after english for students of non-linguistic specialties) - Okopna, Yana (My University, 2010)
The article focuses on the results of the Intelligence Experimental Training of Professionally-Based Dialogical Speech of Future Specialists in the Service Sphere (German after English).
Keywords: бизнес-ролевые игры; business role play; interactional/dialogical speech; second-year students of higher technical educational establishments; бізнес-рольові ігри; интеракций / діалогічного мовлення; студенти другого курсу вищих технічних навчальних закладів; интеракций / диалогической речи; студенты второго курса высших технических учебных заведений; кафедра іноземних мов професійного спрямування